The Effect of Thickers on the Quality of “Indofishme” Instant Noodles as Nutrition Rich Instant Noodles Based on Fish (Scomberomorus Commerson and Seaweed (E.Cottonii): Pengaruh Zat Pengental Terhadap Kualitas Mie Instant “Indofishme” Sebagai Inovasi Mie Instant Kaya Nutrisi Berbasis Ikan Tenggiri (Scomberomorus Commerson) dan Rumput Laut (E.Cottonii) - Nelas, Miftahul Huda; Sumartini; R Nabila; N Hutapea; E Fitriana; N Saputra (Procedia of Social Sciences and Humanities, 2022)
Instant noodles are the most popular substitute for rice in the world, the consumption rate of instant noodles has increased from year to year, in addition, many new innovations have been made by instant noodle manufacturers to increase the selling value of the product. Instant noodle innovations that are widely produced include instant noodles without preservatives, artificial flavorings, and innovations in terms of variants and presentation methods. Indofishme is an instant noodle that has a PIRT permit and is produced with the fortification of fish, seaweed, shrimp waste and seaweed as an effort to reduce gluten content in the use of wheat flour. In this study, the author wants to improve the quality of instant noodles by using CMC. CMC treatments were K0(0%), K1(0.5%), K2 (1%), and K3 (1.5%) with 3 formulations (F1, F2, and F3). The research method is an experimental design using a completely randomized design (CRD) with parameters tested for water absorption, proximate levels, and calorific value. The results of testing water content (8.28-9.94%), fat content (1.57-2.58%), protein content (7.46-14.76%), ash content (1.52-1, 88%), carbohydrate content (75.88-83.75%), water absorption (237.77-364.22%) and calorific value (147.78-278.46 ccal). The results showed that the use of CMC (Carboxyl methylcellulose) can improve the quality of instant noodles (Indofishme). In addition, Indofishme as a new innovative instant noodle based on processed seafood can be used as an alternative to healthy instant noodles because it is richer in nutrients compared to commercial instant noodles.